REV7 counteracts DNA double-strand break resection and affects PARP inhibition - Xu, Guotai; Chapman, J Ross; Brandsma, Inger; Yuan, Jingsong; Mistrik, Martin; Bouwman, Peter; Bartkova, Jirina; Gogola, Ewa; Warmerdam, Daniël; Barazas, Marco; Jaspers, Janneke E; Watanabe, Kenji; et al. (Nature, 2015)
Error-free repair of DNA double-strand breaks (DSBs) is achieved by homologous recombination (HR), and BRCA1 is an important factor for this repair pathway. In the absence of BRCA1-mediated HR, the administration of PARP inhibitors induces synthetic lethality of tumour cells of patients with breast or ovarian cancers. Despite the benefit of this tailored therapy, drug resistance can occur by HR restoration. Genetic reversion of BRCA1-inactivating mutations can be the underlying mechanism of drug resistance, but this does not explain resistance in all cases. In particular, little is known about BRCA1-independent restoration of HR. Here we show that loss of REV7 (also known as MAD2L2) in mouse and human cell lines re-establishes CTIP-dependent end resection of DSBs in BRCA1-deficient cells, leading to HR restoration and PARP inhibitor resistance, which is reversed by ATM kinase inhibition. REV7 is recruited to DSBs in a manner dependent on the H2AX-MDC1-RNF8-RNF168-53BP1 chromatin pathway, and seems to block HR and promote end joining in addition to its regulatory role in DNA damage tolerance. Finally, we establish that REV7 blocks DSB resection to promote non-homologous end-joining during immunoglobulin class switch recombination. Our results reveal an unexpected crucial function of REV7 downstream of 53BP1 in coordinating pathological DSB repair pathway choices in BRCA1-deficient cells.
Keywords: ubikvitinligasy; přesmyk imunoglobulinových tříd; DNA-Binding Proteins; Humans; 53BP1; chromozomální proteiny, nehistonové; DNA Breaks, Double-Stranded; histony; DNA vazebné proteiny; dvouřetězcové zlomy DNA; intracelulární signální peptidy a proteiny; Recombinational DNA Repair; BRCA1 Protein; adaptorové proteiny signální transdukční; Mad2 Proteins; jaderné proteiny; chromatin; ATM protein; lidé; PARP inhibitory; chemorezistence; zvířata; myši; Mad2 protein; Adaptor Proteins, Signal Transducing; Cell Cycle Proteins; Ubiquitin-Protein Ligases; Mice; buněčné linie; Chromatin; Chromosomal Proteins, Non-Histone; Poly(ADP-ribose) Polymerase Inhibitors; Intracellular Signaling Peptides and Proteins; Trans-Activators; Immunoglobulin Class Switching; Cell Line; trans-aktivátory; Histones; protein BRCA1; Nuclear Proteins; Ataxia Telangiectasia Mutated Proteins; proteiny buněčného cyklu; Tumor Suppressor p53-Binding Protein 1; Animals; rekombinační oprava DNA; Drug Resistance, Neoplasm